Pemberdayaan Kelompok Ternak Saiyo Sakato Melalui Pemanfaatan Ransum yang Mengandung Rumput Laut Turbinaria murayana dan Ikan Afkir untuk Meningkatkan Efisiensi dan Produktivitas Ayam Kampung Unggul Balitbangtan (KUB) - Reski, Sepri; Rusli, Ridho Kurniawan; Firdani, Fea; Aritama, Iqbal; Putri, Jihan Nabila; Noorsa, Dion; Cristina, Dina (LPPM Universitas Andalas, 2025)
Rising feed costs and the growing need for sustainable feed resources highlight the importance of utilising locally available ingredients such as seaweed and rejected fish. This community service program aimed to enhance the capacity of the Saiyo Sakato Farmer Group through the innovative use of feed containing Turbinaria murayana seaweed and rejected fish meal, thereby improving the productivity of KUB chickens and reducing feeding costs. The program was implemented in the Saiyo Sakato Farmer Group, Nagari Kambang Barat, Pesisir Selatan Regency, through a series of counselling sessions, hands-on training, and continuous mentoring. The activities included education on KUB chicken management, training on the production of rejected-fish meal, and formulation of rations containing Turbinaria murayana seaweed meal and rejected-fish meal. The results showed significant improvements in the knowledge and skills of group members in utilising Turbinaria murayana and rejected fish as feed ingredients for KUB chickens. The program successfully strengthened farmers’ competencies in adopting low-cost local feed resources, which were more economical than commercial feed, costing only IDR 6,400–7,200 per kilogram. The use of this alternative feed resulted in a 40–46% reduction in feeding costs compared to commercial feed. It improved the productive performance of KUB chickens, achieving an average body weight of 500 g per bird at four weeks of age, a weight gain of 465 g per bird, and 0% mortality.